Source of bigheaded carp (Hypophthalmichthys spp.) in Lake Balaton, Hungary: natural recruitment or continuous escapement from aquaculture?. Issue 2 (3rd April 2017) - Vitál, Zoltán; Józsa, Vilmos; Specziár, András; Mozsár, Attila; Lehoczky, István; Kovács, Balázs; Hliwa, Piotr; Boros, Gergely
Abstract: The worldwide spread of bigheaded carp ( Hypophthalmichthys spp.) is considered an ecological threat and problem in many countries. The aim of this study was to consider the likelihood of bigheaded carp reproduction in Lake Balaton and its catchment area (Hungary). The within-year trends of gonadosomatic index values show that female bigheaded carp increase ovary masses from spring until midsummer, after which a decline is typical. This trend may indicate bulk egg release, but the lack of a sharp drop in fecundity (number of eggs in the ovary) values during and after the potential spawning period suggests that a general and considerable ovary evacuation does not likely explain the declining gonadosomatic index values. Rather, it is more probable that female bigheaded carp resorb their eggs, supported by the presence of atretic oocytes in the ovaries after the potential spawning season. In turn, postovulatory follicles were present in the posterior ovary segments of 2 individuals, indicating that mature eggs were released by some females. The evidence of sporadic egg release does not necessarily imply that successful reproduction has occurred, however. The genetic analyses showed remarkable deviation from Hardy-Weinberg equilibrium within the stock, suggesting that bigheaded carp do not constitute a natural reproductive community in Lake Balaton. Thus, the present bigheaded carp stock in Lake Balaton likely derives primarily from external origin (i.e., from the surrounding fish ponds).